2016
DOI: 10.3390/rs8090690
|View full text |Cite
|
Sign up to set email alerts
|

Drought Forecasting with Vegetation Temperature Condition Index Using ARIMA Models in the Guanzhong Plain

Abstract: This paper works on the agricultural drought forecasting in the Guanzhong Plain of China using Autoregressive Integrated Moving Average (ARIMA) models based on the time series of drought monitoring results of Vegetation Temperature Condition Index (VTCI). About 90 VTCI images derived from Advanced Very High Resolution Radiometer (AVHRR) data were selected to develop the ARIMA models from the erecting stage to the maturity stage of winter wheat (early March to late May in each year at a ten-day interval) of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 47 publications
0
35
0
2
Order By: Relevance
“…Most studies have pointed out that it is insufficient to monitor drought conditions with a single index. T s and vegetation information have been combined for assessing droughts [1,2,4,14,15]. Goward et al (1985), Hope et al (1986), and Nemani et al (1989) found that the slope of the T s /NDVI curve could provide some soil moisture information [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have pointed out that it is insufficient to monitor drought conditions with a single index. T s and vegetation information have been combined for assessing droughts [1,2,4,14,15]. Goward et al (1985), Hope et al (1986), and Nemani et al (1989) found that the slope of the T s /NDVI curve could provide some soil moisture information [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…ARIMA juga cukup baik dalam memodelkan kekeringan pertanian di daerah Guanzhong Cina. Pemodelan tersebut berdasarkan pada data time series yang diperoleh dari hasil pengamatan Vegetation Temperature Condition Index (VTCI) (Tian et al, 2016). Penerapan lain metode ini adalah pada data keberlanjutan dana providet karyawan di Malaysia (Hassan & Othman, 2018).…”
Section: Pendahuluanunclassified
“…To evaluate the influence of wildfire on post-fire vegetation recovery, we estimated an EVI time series for a scenario where the 2011 wildfire did not occur. Various time-series models are applied in remote-sensing vegetation indices such as the linear model autoregressive integrated moving average (ARIMA), or variations developed for dealing with non-stationary data, such as the seasonal ARIMA (SARIMA) [43]. EVI is a nonlinear, nonstationary, and seasonal time series, and the ANN is preferable to other nonlinear time series such as bilinear models, threshold autoregressive models, and regression trees [44].…”
Section: Time-series Prediction Of Post-fire Evimentioning
confidence: 99%